The complete mitochondrial genome of the tartar Sand Boa Eryx tataricus. Issue 1 (2nd January 2019) - Sun, Xiuli; Li, Yaping; Liu, Jia; Sheng, Jun
Abstract: Eryx is a genus of snakes belonging to the family Boidae. In this study, the mitochondrial genome sequence of Eryx tataricus was generated using a PacBio RSII DNA sequencer employing the single molecule, real-time sequencing technology. A maximum-likelihood (ML) phylogenetic tree of 26 snakes was re-constructed based on the 13 protein-coding genes for convincing the mitochondrial DNA sequences.